Population genetic structure revealed by a school of the freshwater migratory fish, Brycon hilarii - Sanches, Alexandra [UNESP]; Galetti, Pedro Manoel (Universidade Católica de Valparaíso, 2012)
It is believed that different genetic populations of migratory fishes can co-exist in a single hydrographic system. Although different populations may occupy and explore the river together, they segregate during the spawning season and consequently the population genetic structuring is maintained. Genetic variation of a Brycon hilarii spawning school and samples from different collection sites in the Miranda River basin were surveyed using seven microsatellites. Population structuring was revealed by a significant differentiation of the spawning school related to the supposed local populations. The genetic differentiation detected may be supported by behavior during the reproductive season that promotes the maintenance of the genetic integrity of different populations. These data may contribute toward the understanding of the behavior and biology of these fish as well as fishery management and species conservation programs.
Keywords: Characidae; Bryconinae; neotropical fish; population structuring; microsatellite; Brasil